Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1073/pnas.92.2.442
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenin antagonists prevent tumor growth in vivo.

Abstract: A noncytotoxic neutralizing monoclonal antibody (mAb), 26-2F, to human angiogenin (Ang), a potent inducer of neovascularization, has been reported to prevent or delay the establishment of HT-29 human tumor xenografts in athymic mice. In the present study the tumor model was modified to increase sensitivity to Ang antagonists to facilitate further investigations and comparisons of their capacity to inhibit tumor growth. An increase in the percentage of tumor-free mice from 10-25% to 65% is observed in this modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
110
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(116 citation statements)
references
References 32 publications
(18 reference statements)
5
110
0
1
Order By: Relevance
“…These results extend previous findings in which angiogenin antagonists, including MAb 26-2F, exerted similar antitumor effects in preclinical models of human colon, lung and fibrosarcoma tumors. 12,13 Our results also showed that the efficacy of MAb 26-2F was significantly improved when it was combined with 2 cytotoxic agents whose activity was minimal when administered without antibody. Further, we demonstrated a profound effect of MAb 26-2F in preventing the formation of regional iliac lymph node metastasis arising from a primary tumor rapidly growing in the prostate of a mouse.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…These results extend previous findings in which angiogenin antagonists, including MAb 26-2F, exerted similar antitumor effects in preclinical models of human colon, lung and fibrosarcoma tumors. 12,13 Our results also showed that the efficacy of MAb 26-2F was significantly improved when it was combined with 2 cytotoxic agents whose activity was minimal when administered without antibody. Further, we demonstrated a profound effect of MAb 26-2F in preventing the formation of regional iliac lymph node metastasis arising from a primary tumor rapidly growing in the prostate of a mouse.…”
Section: Discussionsupporting
confidence: 64%
“…Using antagonists of its activities, we have previously reported that angiogenin plays a crucial role in the subcutaneous (s.c.) growth of human colon, lung and fibrosarcoma tumors in athymic mice, presumably acting at an early stage of tumor development. 12,13 In our work, we extend these studies and show that the neutralizing antiangiogenin monoclonal antibody (MAb) 26-2F similarly inhibits the s.c. establishment of androgen-independent human PC-3 prostate tumor cells in, on average, 40% of the treated mice. Since it has been reported that therapies that combine antiangiogenic treatment with cytotoxic drugs have in some instances resulted in increased efficacy against tumors in mice, experiments of this type were performed in the above PC-3 model system using MAb 26-2F in conjunction with cisplatin and suramin, 2 drugs that have been employed clinically for treating advanced prostate cancer.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…A constituent of normal plasma (6) and milk (7), it is secreted by a wide variety of normal cells (3,8) including those of the placenta (9,10). It has received much attention because of its involvement in the growth of tumors (11)(12)(13)(14)(15). Its expression level is elevated in pancreatic and several other types of cancers (15).…”
mentioning
confidence: 99%
“…Monoclonal antibodies and an antisense oligonucleotide against ANG have proved to be highly effective against several types of cancer in athymic mice (23,24), and clinical studies have shown an association between ANG and cancer (e.g., refs. 25 and 26).…”
mentioning
confidence: 99%